Exploring the impact of consumer behavior and innovation orientation on business strategy and firm performance: Insights from MSMEs in Indonesia (International Journal of Management and Sustainability, 2024)
The purpose of this research is to examine and analyse the influence of consumer behaviour and innovation orientation on firm performance through business strategy, impacting the performance of MSMEs in Karanganyar, Indonesia. The study utilizes a quantitative approach, collecting data through questionnaires and semi-structured interviews with 80 owners of Mbangun Makhutoromo MSMEs Cluster in Karanganyar, Indonesia. The collection data were analysed using linear regression and path analysis with SPSS 24 software. The results indicate that consumer behaviour and innovation orientation significantly impact business strategy. Consumer behaviour has both direct and indirect effects on firm performance through business strategy. On the other hand, innovation orientation affects company performance indirectly through business strategy rather than directly. Enhancing company performance is more effective through direct consumer behaviour analysis. Additionally, well-formulated business strategies can leverage innovation orientation to achieve indirect improvement. For MSMEs to improve performance, a focus on understanding and analysing consumer behaviour is crucial. Business strategies should indirectly employ innovation orientation. This approach requires careful adaptation to environmental changes, consumer preferences, and market trends to ensure sustained business growth and competitiveness.